If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7y = 6(x + y) 2x + 7y = (x * 6 + y * 6) 2x + 7y = (6x + 6y) Solving 2x + 7y = 6x + 6y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 2x + -6x + 7y = 6x + -6x + 6y Combine like terms: 2x + -6x = -4x -4x + 7y = 6x + -6x + 6y Combine like terms: 6x + -6x = 0 -4x + 7y = 0 + 6y -4x + 7y = 6y Add '-7y' to each side of the equation. -4x + 7y + -7y = 6y + -7y Combine like terms: 7y + -7y = 0 -4x + 0 = 6y + -7y -4x = 6y + -7y Combine like terms: 6y + -7y = -1y -4x = -1y Divide each side by '-4'. x = 0.25y Simplifying x = 0.25y
| 12=12+8y | | 5+n=-12 | | 8n+12=3-n+18 | | x+(-20)=-18 | | 6x^2+15x-37=0 | | 3(2x+2)=5(x+1) | | 3cos^2x+7sinx=5 | | 8n+12=-3n+18 | | 20x-40=-80 | | 13+m=-1 | | 2k-6=8+k | | 6a-4+2=3a+1a | | db+x=9(b-d) | | -8b-(-2b)= | | 18x+5-1+8x=46 | | 9n-5=-29+3n | | p-(-11)=11 | | 4z-22=-26+8z | | -6x-32=2 | | 12=9x+3+6 | | p+1=16 | | 60x+75y=9 | | -8+n=-7 | | (-11)-w=(-36) | | 4x-3-7=-27 | | x-(-15)=10 | | 2y-20=35 | | 4x+7+2x=-5x | | -8(9k+7)=15+3k | | 6x-8x+10=9x+19+13 | | r+8=22 | | 5x+2(x-3)+2x=6x+3(x+2)-4+x |